PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI SCRATCH PADA MATA PELAJARAN MATEMATIKA SISWA KELAS III SDN PENGADEGAN 07 JAKARTA SELATAN - Yananda, Arsila; Amelia, Winda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by a lack of understanding and low student learning outcomes in mathematics subjects, especially in length unit material. This happens because the learning process still takes place conventionally, where creative and innovative learning media have not been used. The aim of this research is to develop learning media based on the scratch application for mathematics subjects for class III students at SDN Pengadegan 07 South Jakarta and to determine the feasibility and effectiveness of this media. This research uses the Research and Development (R&D) method with the Dick and Carey development model through 10 development stages. The types of data used are quantitative data and qualitative data. The instruments used are interviews, questionnaires and tests. The data collection techniques used were interviews, observation and questionnaires. The results obtained from the development of scratch application-based learning media products are based on the feasibility results of the design expert validator at 80%, the language expert validator at 84%, the material expert validator at 80% and the results of the feasibility test in small groups obtained at 82% and the test results feasibility in the large group was obtained at 86%. Furthermore, the results of the effectiveness of learning media products in small group trials were obtained at 0.45 with medium success criteria and the results for the effectiveness of learning media products in large group trials were obtained at 0.45 with medium success criteria based on the normality gain (N-gain) test.